A is addition
b is subtraction
c is division
Answer:
The two factors will be
Step-by-step explanation:
We have given the equation ![9-16x^4](https://tex.z-dn.net/?f=9-16x%5E4)
We know the algebraic equation ![a^2-b^2=(a+b)(a-b)](https://tex.z-dn.net/?f=a%5E2-b%5E2%3D%28a%2Bb%29%28a-b%29)
As
can be written as
, as square of 3 is 9 and square of
is ![16x^4](https://tex.z-dn.net/?f=16x%5E4)
So ![9-16x^4=3^2-(4x^2)^=(3+4x^2)(3-4x^2)](https://tex.z-dn.net/?f=9-16x%5E4%3D3%5E2-%284x%5E2%29%5E%3D%283%2B4x%5E2%29%283-4x%5E2%29)
So the two factors will be ![=(3+4x^2)\ and\ (3-4x^2)](https://tex.z-dn.net/?f=%3D%283%2B4x%5E2%29%5C%20and%5C%20%283-4x%5E2%29)
7900 79 times 100 ------------
Answer:
![\sqrt[3]{x^{2}}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7Bx%5E%7B2%7D%7D)
Step-by-step explanation:
![x^{2/3} = \sqrt[3]{x^{2}}](https://tex.z-dn.net/?f=x%5E%7B2%2F3%7D%20%3D%20%5Csqrt%5B3%5D%7Bx%5E%7B2%7D%7D)